The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/cas.12844
|View full text |Cite
|
Sign up to set email alerts
|

Long non‐coding RNA urothelial cancer‐associated 1 promotes bladder cancer cell migration and invasion by way of the hsa‐miR‐145–ZEB1/2–FSCN1 pathway

Abstract: Numerous studies suggest that several long non‐coding RNAs (lncRNAs) play critical roles in bladder cancer development and progression. Long non‐coding RNA urothelial cancer‐associated 1 (lncRNA‐UCA1) is highly expressed in bladder cancer tissues and cells, and it has been shown to play an important role in regulating aggressive phenotypes of bladder cancer cells. However, little is known about the molecular mechanism of lncRNA‐UCA1‐mediated bladder cancer cell migration and invasion. Here, we show that overex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
112
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(123 citation statements)
references
References 44 publications
(54 reference statements)
6
112
0
Order By: Relevance
“…UCA1 is a sensitive and specific oncogenic lncRNA in bladder cancer (16). Consistent with previous observations that high UCA1 expression was involved in cell invasion in many cancers as well as bladder cancer (24,36,37), our results clearly showed that cells with stronger invasion capabil ity had higher UCA1 expression levels in bladder cancer cell lines in vitro. EMT is a well-characterized process that facilitates invasion and metastatic dissemination of human cancers (3,4).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…UCA1 is a sensitive and specific oncogenic lncRNA in bladder cancer (16). Consistent with previous observations that high UCA1 expression was involved in cell invasion in many cancers as well as bladder cancer (24,36,37), our results clearly showed that cells with stronger invasion capabil ity had higher UCA1 expression levels in bladder cancer cell lines in vitro. EMT is a well-characterized process that facilitates invasion and metastatic dissemination of human cancers (3,4).…”
Section: Discussionsupporting
confidence: 91%
“…To investigate the potential mechanism by which UCA1 regulates EMT in bladder cancer cells, we examined the effect of UCA1 on the expression of HMGB1, which is reported to be associated with the invasion ability of many types of human cancers including bladder cancer (24). qRT-PCR showed that HMGB1 mRNA expression was significantly (P<0.05) reduced by knockdown of UCA1 in T24 cells and increased by overexpression of UCA1 in RT4 cells (Fig.…”
Section: Uca1 Promoted the Invasion And Emt Of Bladder Cancer Cells Bmentioning
confidence: 99%
See 2 more Smart Citations
“…In vitro study revealed that MVIH could promote cell proliferation and cell cycle, while inhibiting apoptosis of breast cancer cells. Xue et al (2016) reported that lncRNA urothelial cancer-associated 1 (UCA1) promoted the migration and invasion of bladder cancer cells via regulating the miR-145/ zinc finger E-box binding homeobox 1 and 2 (ZEB1 and ZEB2)/fascin homologue 1 (FSCN1) pathway. Therefore, understanding the exact roles of specific lncRNAs may contribute to the development of the diagnostics and therapeutics of human cancers.…”
Section: Discussionmentioning
confidence: 99%